Learning of a Golf Putting Task with Varying Contextual Interference Levels Induced by Feedback Schedule in Novices and Experts. Issue 2 (April 2014) - Krause, Daniel; Brüne, Alexander; Fritz, Susanne; Kramer, Pascal; Meisterjahn, Peter; Schneider, Michael; Sperber, Alena
Switching between tasks during practice can affect motor learning. This study tested whether switching feedback content has any effects on learning to perform golf putts without full visibility. 60 participants (44 men, 16 women; M age = 26.3 yr., SD = 6.6) practiced golf putts without seeing the ball movement. 30 of the participants were golfers with moderate expertise, and 30 were novices. They received feedback regarding their putts, either on the angle or on the distance in one of three feedback schedules: blocked, serial-blocked, or serial. Independent of the expertise level, learning was not affected by the feedback schedule. The strong linkage between the two components—direction and distance—may have prevented a sufficient level of contextual interference.